P282 Isolated colonic Crohn's disease and extensive ulcerative colitis: is there a reel difference?. (30th January 2023) - Ben Safta, N; Ben Mustpha, N; Khemiri, W; Serghini, M; Laabidi, S; Fekih, M; Labidi, A; Boubaker, J
Abstract: Background: The management of isolated colonic Crohn's disease (CDc) is often modeled on that of Ulcerative Colitis (UCc). The aim of our study was to compare epidemiological and evolutive profiles of CDc and UCc. Methods: We conducted a retrospective, descriptive and comparative study, including patients diagnosed with CDc as well as UCc, who were hospitalized in our department over a 9-year period [January 2011 - January 2020]. The group 1 included patients with CDc and group 2 included patients with UCc. Patients with less than 2 years of follow-up were excluded. Data were recorded and analyzed by SPSS software version 26. Results: We included 130 patients with a sex ratio M/F= 0.68. The mean age at diagnosis was 34.85 years [6-68 years]. Sixty-three patients had CDc, while 67 patients had UCc. The two groups were comparable for age (p=0.56) and sex (p=0.54). The percentage of patients with smoking and alcoholism was also comparable between the two groups (p=0.4 and p=0.8 respectively). The presence of at least one autoimmune disease and a family history of Inflammatory Bowel Disease were more noted in patients in group 1 than in group 2 (p= 0.011 and p=0.046 respectively). The mean BMI at diagnosis was 22.28 kg/m² and was comparable between the 2 groups. The main phenotype was inflammatory (93.6%) in group 1. Twenty-five patients in group 1 (39.6%) and 22 patients (32.8%) in group 2 had associated extra-intestinal involvement (p=0.41), represented mainly by rheumatological involvement (n=39, 30%). The mean albumin level at diagnosis was 29.21 g/L and 30.96 g/L in groups 1 and 2 respectively. The occurrence of Severe Acute Colitis during follow-up was more frequent in group 2 than in group 1 (58.2% vs. 46%), although the difference was not significant (p=0.13). However, the rate of colectomy was significantly higher in group 2 (p=0.029). The use of anti-TNF therapy was significantly higher in group 1 (p=0.046). The maximum duration of hospitalization and the number of relapses were not statistically different between the 2 groups (p=0.81 and p=0.8 respectively). Finally, there was no significant difference between the 2 groups considering the use of corticosteroid or immunosuppressive therapy (p=0.88 and p=0.96 respectively). The main limit of our study is that it was conducted only in hospitalized patients who had relatively severe disease. Conclusion: CDc is more prone to intensive medical treatment, whereas colectomy is more noted in UCc.